Description of the determinants of stunting events in children in the work area of Pangale Health Center - Husna, Asmaul; Bujawati, Emmi; Aeni, Syahratul (Unified Health Critical Research, 2025)
Stunting is associated with the risk of morbidity and mortality, poor brain development, as well as slow motor skill development and mental retardation. This research is a quantitative research with a descriptive approach. The population in this study were stunted toddlers in the Puskesmas working area with a total sample of 83 samples using a total sampling technique . The collected data was then analyzed univariately. The results showed that from a total of 83 samples, most of them were male (50.6%), most of the mothers with elementary school education/equivalent were 33 people (39.8%), most of them had fathers who worked as farmers as many as 55 people (66.3%). The majority of mothers work as IRT as many as 75 people (90.4%). Stunting toddlers have fathers with short height categories as many as 66 people (81.5%) and most of them have mothers with short height categories as many as 72 people (86.7%). With parents whose income is < Rp 1,000,000.00 per month as many as 29 toddlers (34.9%), most of the toddlers do not have a history of LBW as many as 69 toddlers (83.1%), having a history of complete immunization as many as 77 toddlers (92 ,8%) and did not have a history of exclusive breastfeeding, namely 49 toddlers (59.0%). Therefore, the researcher recommends that the Puskesmas provide additional education to mothers about stunting and the importance of exclusive breastfeeding at posyandu.